User Interface Design for Grab Merchant Application Version 4.18.0 with Usability Approach - Weny Fdiasindiastuti,; Ari Basuki,; Rullie Annisa,; Fitri Agustina,; Faikul Umam,; Retno Indiartiningtias, (Technium: Romanian Journal of Applied Sciences and Technology, 2023)
The development of technology is increasingly rapid, providing convenience in various aspects of activities. This has also penetrated business actors so that they can easily access the products and services they offer to many customers. This can take advantage of current technology through smartphone applications. Grab Merchant is an application that offers food and beverage orders that are delivered according to customer needs. However, we found problems with the usability of application features, especially controlling stock from the user side. The purpose of this study is to measure usability of the Grab Merchant application, researchers use the Use Questionnaire method to propose design user interface. The user interface design that is built is an improvement on features in accordance with the results of the distributed questionnaire. The research focus consists of 3 basic aspects of usability measurement, namely effectiveness, efficiency and satisfaction. These three aspects are measured by indicators of Usefulness, Ease of Use, Ease of Learning and Satisfaction in the Use Questionnaire method. As a result, improvements were made to the user interface design of the interface on the features and there was an increase in these 3 indicators.